Unilateral Corneal Insult Also Alters Sensory Nerve Activity in the Contralateral Eye - Luna, Carolina; Quirce, Susana; Aracil-Marco, Adolfo; Belmonte, Carlos; Gallar, Juana; Acosta, M. Carmen (Frontiers in Medicine, 2021)
After unilateral inflammation or nerve lesion of the ocular surface, the ipsilateral corneal sensory nerve activity is activated and sensitized, evoking ocular discomfort, irritation and pain referred to the affected eye. Nonetheless, some patients with unilateral ocular inflammation, infection or surgery reported discomfort and pain also in the contralateral eye. We explored the possibility that such altered sensations in the non-affected eye are due to changes in their corneal sensory nerve activity in the contralateral, not directly affected eye. To test that hypothesis, we recorded ex vivo the impulse activity of corneal mechano- and polymodal nociceptor, and of cold thermoreceptor nerve terminals in both eyes of guinea pigs subjected unilaterally to three different experimental conditions (UV-induced photokeratitis, microkeratome corneal surgery, and chronic tear deficiency caused by removal of the main lacrimal gland), and in eyes of naïve animals. Overall, after unilateral eye damage, corneal sensory nerve activity appeared altered also in the contralateral eye. Compared with naïve guinea-pigs, animals with unilateral UV-induced mild corneal inflammation, showed on both eyes and inhibition of spontaneous and stimulus-evoked activity of cold thermoreceptors, and increased activity in nociceptors affecting both the ipsilateral and the contralateral eye. Unilateral microkeratome surgery affected mostly the activity of nociceptors, inducing sensitization in both eyes. Removal of the main lacrimal gland reduced tear volume and increased cold thermoreceptor activity in both eyes. This is the first direct demonstration that unilateral corneal nerve lesion, especially ocular surface inflammation, affects functionally the activity of the different types of corneal sensory nerves in both the ipsilateral and the contralateral eye. The mechanisms underlying the contralateral affectation of sensory nerves remain to be determined, although available data support the involvement of neuroimmune interactions. The parallel alteration of nerve activity in contralateral eyes has two main implications: a) in the experimental design of both preclinical and clinical studies, where the contralateral eyes cannot be considered as a control; and, b) in the clinical practice, where clinicians must consider the convenience of treating both eyes of patients with unilateral ocular conditions to avoid pain and secondary undesirable effects in the fellow eye.